Special features of radio pulse spectral density analysis - Chubykalo, Andrew; Espinoza, Augusto; Kuligin, Victor (CIENCIA ergo-sum; Vol. 27 Núm. 4 (2020): Número especial "Retos de la física no lineal", 2020)
The spectrum analysis of the periodic sequence radio pulses is often described in textbooks. However, if this method is applied to short radio pulses with a large period between them, then large errors occur. In this article, we described a new method of pulse gating. This method allows us to measure the spectral density of radio signals with high duty cycle. The main advantages of our method are a high signal-to-noise ratio, a large dynamic range of measurements, and a higher accuracy of spectral density measurements.